Security of self-organizing networks: MANET, WSN, WMN, VANET - Pathan, Al-Sakib Khan (Auerbach Publications, CRC Press, Taylor & Francis Group, 2011)
Reflecting cutting-edge advancements, Security of Self-Organizing Networks: MANET, WSN, WMN, VANET explores wireless network security from all angles. It begins with a review of fundamental security topics and often-used terms to set the foundation for the following chapters. Examining critical security issues in a range of wireless networks, the book proposes specific solutions to security threats.